Flexible Bronchoscopy for Pulmonary Bleeding and Endobronchial Blood Clot Obstruction in Patients on Extra-Corporeal Membrane Oxygenation: A Case Series - Lisa Maria Valiyaveettil; Carolin Steinack; Malcolm Kohler; Silvia Ulrich; Sascha David; Thomas Gaisl (Journal of Clinical Medicine, 2026)
Background: Extracorporeal membrane oxygenation (ECMO) is a life-saving organ support for severe circulatory or respiratory failure, but it is frequently complicated by bleeding. Pulmonary haemorrhage and consecutive airway obstruction are major contributors to morbidity and mortality. Flexible bronchoscopy (FB) is indispensable for diagnosing and managing pulmonary bleeding; however, its safety and efficacy in ECMO patients remain insufficiently studied. This analysis evaluated the feasibility, safety, and short-term physiological effects of FB in critically ill adults supported with ECMO. Methods: In this single-centre retrospective study, all adult ECMO patients who underwent FB for endobronchial bleeding or obstructive clot formation between January 2020 and December 2024 at the University Hospital Zurich were included. The procedural indications, diagnostic findings, haemostatic interventions, anticoagulation management, and oxygenation parameters before and after FB were analysed. The bleeding severity was graded according to the level of intervention required for haemostasis. Results: Sixteen patients (median age: 51.5 years, 69% male) underwent 34 FB procedures while on ECMO (69% veno-arterial). Most procedures were therapeutic (71%) and performed for haemorrhage (35%) or airway obstruction (21%). Clot removal was attempted in 85% of bronchoscopies, achieving partial or complete clearance in most cases. The median PaO2/FiO2 ratio improved from 142.8 mmHg to 161.4 mmHg (post/pre ratio: 1.36); requiring a lower FiO2 (p = 0.049). Of the procedures performed for active bleeding, 24% were classified as severe, and bronchial blockers were required in 26%. Bleeding control failed in 12% of cases. The ICU mortality was 62.5%, with pulmonary haemorrhage directly causing death in 25%. Conclusions: FB is feasible in ECMO patients and provides a measurable short-term improvement in oxygenation. However, the high mortality underscores the severity of the underlying disease. Repeat FB likely reflects the disease burden rather than procedural inefficacy.